The heme‐binding protein Dap1 links iron homeostasis to azole resistance via the P450 protein Erg11 in Candida glabrata. Issue 4 (8th April 2013) - Hosogaya, Naoki; Miyazaki, Taiga; Nagi, Minoru; Tanabe, Koichi; Minematsu, Asuka; Nagayoshi, Yohsuke; Yamauchi, Shunsuke; Nakamura, Shigeki; Imamura, Yoshifumi; Izumikawa, Koichi; Kakeya, Hiroshi; Yanagihara, Katsunori; et al.
Abstract The pathogenic fungus Candida glabrata is relatively resistant to azole antifungals, which target lanosterol 14α‐demethylase (Erg11p) in the ergosterol biosynthesis pathway. Our study revealed that C. glabrata exhibits increased azole susceptibility under low‐iron conditions. To investigate the molecular basis of this phenomenon, we generated a strain lacking the heme (iron protoporphyrin IX)‐binding protein Dap1 in C. glabrata. The Δdap1 mutant displayed growth defects under iron‐limited conditions, decreased azole tolerance, decreased production of ergosterol, and increased accumulation of 14α‐methylated sterols lanosterol and squalene. All the Δdap1 phenotypes were complemented by wild‐type DAP1, but not by DAP1D91G, in which a heme‐binding site is mutated. Furthermore, azole tolerance of the Δdap1 mutant was rescued by exogenous ergosterol but not by iron supplementation alone. These results suggest that heme binding by Dap1 is crucial for Erg11 activity and ergosterol biosynthesis, thereby being required for azole tolerance. A Dap1‐GFP fusion protein predominantly localized to vacuolar membranes and endosomes, and the Δdap1 cells exhibited aberrant vacuole morphologies, suggesting that Dap1 is also involved in the regulation of vacuole structures that could be important for iron storage. Our study demonstrates that Dap1 mediates a functional link between iron homeostasis and azole resistance in C. glabrata.